Bilateral borderline ovarian cystadenoma with migration of intrauterine device to right ovary accompanied with endometrial carcinoma in situ: a case report - G. Zhu; S.J. Liu; W. Lv (Clinical and Experimental Obstetrics & Gynecology)
Synchronous bilateral borderline ovarian cystadenoma and endometrial cancer are rare in clinical practice which could easily cause some confusion in the diagnosis of primary tumor lesions. On the other hand, it is common for the intrauterine device (IUD) to migrate to the uterine muscle wall, pelvic cavity, abdominal cavity, intestinal canal and broad ligament etc. However, IUD migration to the ovary is rare. In this paper, a case of bilateral borderline ovarian cystadenoma with migration of IUD into the right ovary accompanied with endometrial carcinoma in situ is first reported.